Estimate of soil loss due to Cassava harvesting from farmlands in Southwest of Nigeria - OLOGUNDE, OLANREWAJU HAMEED; BUSARI, MUTIU ABOLANLE; OLOWOKERE, FLORENCE ALABA; BHATT, RAJAN; ARORA, SANJAY (Journal of Soil and Water Conservation, 2024)
The cultivation of cassava has been attributed to soil degradation through soil loss by water erosion. However, the magnitude of soil loss due to harvesting cassava (Manihot esculentus) is understudied. This study assessed the amount of soil and nutrient losses due to cassava manual harvesting from farmlands in Southwest Nigeria and investigated the factors that affect soil losses. Cassava harvesting was conducted twice at 8 locations in southwest Nigeria. The plant and soil samples were analyzed for planting density, root yield, soil texture, soil moisture, organic carbon, nitrogen, available phosphorus and potassium contents. The average soil loss from cassava harvesting was estimated as 8.35 t ha-1 harvest-1. The mean nutrient loss from the field was 9.95 kg N ha-1 harvest-1, 0.10 kg P ha-1 harvest-1 and 0.61 kg K ha-1 harvest-1. Clay content, soil moisture content, and root yield correlated positively with crop specific soil loss with correlation coefficients of 0.12, 0.53, and 0.57, respectively. Soil moisture and root yield are important factors that contribute to soil loss due to cassava harvesting. The high amount of soil and nutrient losses suggest that cassava harvesting could contribute to soil degradation in areas with high cassava root production. Therefore, further investigation should be conducted on harvesting procedures to minimize soil losses.